2012
DOI: 10.1614/wt-d-11-00083.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Thermal Implements and Organic Herbicides for Weed Control in a Nonbearing Almond (Prunus dulcis) Orchard

Abstract: Sustainable weed management strategies are needed for organic orchard systems. A study was conducted in an almond orchard in Fresno, CA from 2009 to 2011. Treatment comparisons included steam, flame, and broad applications of either lemongrass oil or D-limonene. An untreated control was also included. The experimental design was a randomized complete block with four replications. Weekly evaluations on percent weed control were taken and weed biomass was sampled 4 to 8 wk after treatment (WAT). Weed control and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 15 publications
2
15
0
2
Order By: Relevance
“…However, most of the younger weeds also regrew within a few weeks. These results support other recent findings suggesting that steam has differential effects on various weed species, with succulent weeds and grasses being poorly controlled compared with some other broadleaved weed species (Leon and Ferreira, 2008;Shrestha et al, 2012).…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…However, most of the younger weeds also regrew within a few weeks. These results support other recent findings suggesting that steam has differential effects on various weed species, with succulent weeds and grasses being poorly controlled compared with some other broadleaved weed species (Leon and Ferreira, 2008;Shrestha et al, 2012).…”
Section: Resultssupporting
confidence: 91%
“…The steam generating machine was equipped with a propane-powered burner that combusted propane and delivered steam through an adjustable sidearm (canopy). More details of the machine are available in Shrestha et al (2012). The machine was pulled by a tractor at a travel speed of 1.5 mph.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another increasingly used weed control method is thermal weed control. Thermal weed control can be used in various crops (Shrestha et al, 2013;Velička et al, 2016) In different countries, diverse methods of thermal weed control are used in organic farms: flaming (Sivesind et al, 2012), combustion gases (Ulloa et al, 2010;2012;Datta, Knezevic, 2013), hot foam (Cederlund, Börjesson, 2016), hot water (De Cauwer et al, 2014) and water steam (Melander, Kristensen, 2011;Shrestha et al, 2012;Vidotto et al, 2013). Researchers have indicated that thermal weed control is more effective than mechanical weed control (Virbickaitė et al, 2006;Ascard et al, 2007).…”
Section: Introductionmentioning
confidence: 99%